METHOD FOR MANUFACTURING WHEAT FLAKES USING UV IRRADIATION - Бажай-Жежерун, Світлана; Федоренко, Тетяна; Тогачинська, Ольга (Modern engineering and innovative technologies, 2025)
We have developed a method for the production of wheat flakes for health purposes, which includes grain preparation for processing, washing and disinfection, peeling, hydrothermal treatment at a temperature of 12 - 16 ºС in three cycles, each of which inc